Toxicity of Copper Oxide (CuO) Nanoparticles on Human Blood Lymphocytes - Assadian, Evelyn; Zarei, Mohammad Hadi; Gilani, Ali Ghanadzadeh; Farshin, Mehrzad; Degampanah, Hamid; Pourahmad, Jalal (Biological trace element research, 2018)
CuO nanoparticles (CuO-NPs) serve several important functions in human life, particularly in the fields of medicine, engineering, and technology. These nanoparticles have been utilized as catalysts, semiconductors, sensors, gaseous and solid ceramic pigments, and magnet rotatable devices. Further use for CuO-NPs has been employed in the pharmaceutical industry especially in the production of anti-microbial fabric treatments or prevention of infections caused by Escherichia coli and methicillin-resistant Staphylococcus aureus . Two key potential routes of exposure to CuO-NPs exist through inhalation and skin exposure. Toxicity of these nanoparticles has been reported in various studies; however, no study as of yet has investigated the complete cellular mechanisms involved in CuO-NPs toxicity on human cells. The aim of this study was to determine the cytotoxicity of CuO-NPs on human blood lymphocytes. Blood lymphocytes were obtained from healthy male subjects through the use of Ficoll polysaccharide subsequently by gradient centrifugation. The following parameters were assayed in blood lymphocytes after a 6-h incubation with different concentrations of CuO-NPs: cell viability, reactive oxygen species (ROS) formation, lipid peroxidation, cellular glutathione levels, and mitochondrial and lysosomal damage. Our results demonstrate that CuO-NPs, in particular, decreased cell viability in a concentration-dependent manner and the IC50 determined was 382 μM. CuO-NP cytotoxicity was associated with significant increase at intracellular ROS level and loss of mitochondrial membrane potential and lysosomal membrane leakiness. Hence, CuO-NPs are shown to effectively induce oxidative stress in addition to inflict damage on mitochondria and lysosomes in human blood lymphocytes.